Diaspora Orang Arab di Kota Medan: Sejarah dan Interaksi Sosial Komunitas Alawiyyin pada Abad ke-20 - Taslim Batubara; Hasan Asari; Faisal Riza (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2020)
This article discusses the history of the arrival of the Arabs, especially the Sayyid group, to Medan. The Sayyid group began to come to Medan around the 19th century. On average, their arrival was motivated to trade, only a small proportion of them came with the intention of spreading Islam. This study uses the historical method in four writing steps, namely; heuristics, verification or criticism, interpretation, and historiography, with a social approach. Since the widespread cultivation of Deli Tobacco in Medan, Medan has turned into an area that is crowded with immigrants from all over the world. Moreover, since it was made the Capital of the Residency of East Sumatra in 1889, Medan has become the most developed city on the East Coast of Sumatra. The presence of Arabs in this area made Medan a city with a very diverse population. Since the beginning of his arrival, Arab social interactions have been going well and have never experienced conflicts with other ethnicities, but have been warmly welcomed. Apart from that, the presence of Arabs also had an impact on the life of the people of Medan City, such as in the fields of: religion, trade, marriage and the arts.